L.A. city limits : African American Los Angeles from the Great Depression to the present - Sides, Josh, 1972- (University of California Press, 2003)
In 1964 an Urban League survey ranked Los Angeles as the most desirable city for African Americans to live in. In 1965 the city burst into flames during one of the worst race riots in the nation's history. How the city came to such a pass--embodying both the best and worst of what urban America offered black migrants from the South--is the story told for the first time in this history of modern black Los Angeles.